Faces of justice in the video game Lost Judgment - Puspa Jelita, Intan Annisya; Saleha Gandana, Isti Siti (Passage: Journal of English Language and Literature, 2025)
Video games are significant subjects in cultural studies because they are considered cultural artifacts. Like literary works, video games often incorporate social concepts and elements, such as justice, that are derived from real life. While much research has been conducted on fairness in video games, most studies focus on the perspectives of players and game developers. This study aims to explore the types of justice exercised by the protagonist and main antagonist of Lost Judgment and to understand the reasons behind their choices. The data were gathered from the dialogues between the two characters, with the types of justice identified using Deutsch et al.'s (2011) framework. The analysis was conducted through Smith’s (2017) textual analysis. The findings reveal that the protagonist, Takayuki Yagami, embodies distributive justice, while the antagonist, Jin Kuwana, represents retributive justice. Both characters share similar motivations for their perspectives on justice: traumatic experiences in their respective careers that left them with deep regret. Their views on justice are also influenced by their shared belief that the current legal system is flawed, prompting them to take justice into their own hands. This research concludes that the justice portrayed by the main characters of Lost Judgment reflects the game developer’s commentary on justice, as their traits are tied to issues that are particularly relevant in Japan.